Stereotactic Body Radiotherapy as an Alternative to Brachytherapy in Gynecologic Cancer - Kubicek, Gregory J. (Hindawi Publishing Corporation, 2013)
Introduction. Brachytherapy plays a key role in the treatment of many gynecologic cancers. However, some patients are unable to tolerate brachytherapy for medical or other reasons. For these patients, stereotactic body radiotherapy (SBRT) offers an alternative form of treatment. Methods. Retrospective review of patients prospectively collected on SBRT database is conducted. A total of 11 gynecologic patients who could not have brachytherapy received SBRT for treatment of their malignancies. Five patients have been candidates for interstitial brachytherapy, and six have required tandem and ovoid brachytherapy. Median SBRT dose was 25 Gy in five fractions. Results. At last followup, eight patients were alive, and three patients had died of progressive disease. One patient had a local recurrence. Median followup for surviving patients was 420 days (median followup for all patients was 120 days). Two patients had acute toxicity (G2 dysuria and G2 GI), and one patient had late toxicity (G3 GI, rectal bleeding requiring cauterization). Conclusions. Our data show acceptable toxicity and outcome for gynecologic patients treated with SBRT who were unable to receive a brachytherapy boost. This treatment modality should be further evaluated in a phase II study.